Risk and Reliability Analysis: Theory and Applications In Honor of Prof. Armen Der Kiureghian - Gardoni, Paolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents a unique collection of contributions from some of the foremost scholars in the field of risk and reliability analysis. Combining the most advanced analysis techniques with practical applications, it is one of the most comprehensive and up-to-date books available on risk-based engineering. All the fundamental concepts needed to conduct risk and reliability assessments are covered in detail, providing readers with a sound understanding of the field and making the book a powerful tool for students and researchers alike. This book was prepared in honor of Professor Armen Der Kiureghian, one of the fathers of modern risk and reliability analysis.
Risk and Reliability Analysis -- Structural System Reliability, Reloaded -- Global Buckling Reliability Analysis of Slender Network Arch Bridges: An Application of Monte Carlo-based Estimation by Optimized Fitting -- Review of Quantitative Reliability Methods for Onshore Oil and Gas Pipelines -- An Intuitive Basis of the Probability Density Evolution Method (PDEM) for Stochastic Dynamics -- The Tail Equivalent Linearization Method for Nonlinear Stochastic Processes, Genesis and Developments -- Estimate of Small First Passage Probabilities of Nonlinear Random Vibration Systems -- Generation of Non-synchronous Earthquake Signals -- Seismic Response Analysis with Spatially Varying Stochastic Excitation -- Application of CQC Method to Seismic Response Control with Viscoelastic Dampers. .
Keywords: Security systems; Probabilities; Statistics .; Security Science and Technology; Probability Theory; Statistics in Engineering, Physics, Computer Science, Chemistry and Earth Sciences